Identification of clay mineral compounds in the Southern Iraqi upper Nahr Umar Formation using SGR logging - Kadhim, Mahdi M.; Abdul Hussein, Hassan A.; Dheyauldeen, Atheer (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Typically, sandstone oil reserves comprise various clay minerals, such as illite, chlorite, and kaolinite. The existence of these clay minerals drastically affected the quality of these reservoirs. This paper attempts to detect clay minerals and environmental deposition of the upper shaly-sand unit (USSU) of the Nahr Umar formation, as it is the main reservoir. It is a portion of an anticline composed of a lower Cretaceous clastic sandstone formation. The kind of environment, clay minerals, and depositional correlation between total organic matter and uranium content were determined using a spectral log of gamma-ray (SGR). According to the SGR log, the primary constituents of USSU are mixed-layer clays, which are illite, kaolinite, and chlorite. The investigated wells in the field's western north have Th/U (thorium/ uranium) ratios ranging from 0.465 to 18.4. Based on the Th/U ratio, the USSU had a mostly shallow marine with continental and marine environment traces. Additionally, a Th/K (thorium /potassium) cross-plot revealed that as kaolinite decreased, illite increased in the formation's southern region.